(3x²ᵃ - 4yᵃz³ᵃ)² =
= 9x⁴ᵃ - 12x²ᵃyᵃz³ᵃ + 16y²ᵃz6ᵃ
Answer:
True
Step-by-step explanation:
This is true. x + 25 equals 40 in both cases, so they're equal.
Answer:
it's just shaked photo I can't even understand sorry for not helping you
Step-by-step explanation:
here is your answer hope you will enjoy and mark me as brain list
thank you
Answer:
y-determinant = 2
Step-by-step explanation:
Given the following system of equation:
Let's represent it using a matrix:
![\left[\begin{array}{ccc}1&2\\1&-3\end{array}\right] = \left[\begin{array}{ccc}5\\7\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%5C%5C1%26-3%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D5%5C%5C7%5Cend%7Barray%7D%5Cright%5D)
The y‐numerator determinant is formed by taking the constant terms from the system and placing them in the y‐coefficient positions and retaining the x‐coefficients. Then:
![\left[\begin{array}{ccc}1&5\\1&7\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%265%5C%5C1%267%5Cend%7Barray%7D%5Cright%5D%20)
y-determinant = (1)(7) - (5)(1) = 2.
Therefore, the y-determinant = 2